Differences between germline and somatic mutation rates in humans and mice - Brandon Milholland (Nature Portfolio, 2017)
Germline mutation rates are known to vary between species but somatic mutation rates are less well understood. Here the authors compare mice and humans, observing that somatic mutation rates were nearly two orders of magnitude higher in both species, with both mutation rates significantly higher in mice.